Deep CO2 in the end-Triassic Central Atlantic Magmatic Province - Capriolo, Manfredo; Marzoli, Andrea; Aradi, László E.; Callegaro, Sara; Dal Corso, Jacopo; Newton, Robert J.; Mills, Benjamin J. W.; Wignall, Paul B.; Bartoli, Omar; Baker, Don R.; Youbi, Nasrrddine; Remusat, Laurent; et al. (Nature Communications, 2020)
Large Igneous Province eruptions coincide with many major Phanerozoic mass extinctions, suggesting a cause-effect relationship where volcanic degassing triggers global climatic changes. In order to fully understand this relationship, it is necessary to constrain the quantity and type of degassed magmatic volatiles, and to determine the depth of their source and the timing of eruption. Here we present direct evidence of abundant CO2 in basaltic rocks from the end-Triassic Central Atlantic Magmatic Province (CAMP), through investigation of gas exsolution bubbles preserved by melt inclusions. Our results indicate abundance of CO2 and a mantle and/or lower-middle crustal origin for at least part of the degassed carbon. The presence of deep carbon is a key control on the emplacement mode of CAMP magmas, favouring rapid eruption pulses (a few centuries each). Our estimates suggest that the amount of CO2 that each CAMP magmatic pulse injected into the end-Triassic atmosphere is comparable to the amount of anthropogenic emissions projected for the 21(st) century. Such large volumes of volcanic CO2 likely contributed to end-Triassic global warming and ocean acidification. Many major mass extinction events have been associated with large volcanic eruption events, with the argument that large volumes of volcanic degassing could trigger past global climate changes. Here, the authors find that during the end-Triassic extinction event volcanic pulses emitted large amounts of CO2 comparable to projected anthropogenic emissions for the 21(st) century in the future 2 degrees C warming scenario.